2014
DOI: 10.30770/2572-1852-100.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Medical Board Complaints against Physicians Due to Communication: Analysis of North Carolina Medical Board Data, 2002–2012

Abstract: Anecdotal evidence suggests that communication issues are one of the primary reasons for physician complaints, but quantitative studies have yet to examine this assertion. The North Carolina Medical Board's Complaint Department maintains data on physician complaints and categorizes each complaint based on its primary cause. Using data from 2002–2012, our research focused on complaints against physicians licensed by the North Carolina board to determine the extent to which communication issues contribute to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on the feedback we have already received, we are likely to increase emphasis on subjects particularly important to medical practice (e.g., clinical reasoning) and areas in which state medical boards identify deficiencies (e.g., communication). 5 The initial enhancements to clinical skills assessment in USMLE exams will augment current formats and integrate them into the existing exam structure. To the extent possible, content revisions identified through stakeholder input may be reflected in multiple-choice questions in all 3 Step exams and/or computer case simulations in the Step 3 exam.…”
Section: Looking To the Futurementioning
confidence: 99%
“…Based on the feedback we have already received, we are likely to increase emphasis on subjects particularly important to medical practice (e.g., clinical reasoning) and areas in which state medical boards identify deficiencies (e.g., communication). 5 The initial enhancements to clinical skills assessment in USMLE exams will augment current formats and integrate them into the existing exam structure. To the extent possible, content revisions identified through stakeholder input may be reflected in multiple-choice questions in all 3 Step exams and/or computer case simulations in the Step 3 exam.…”
Section: Looking To the Futurementioning
confidence: 99%
“…1 Communication with patients and families is a fundamental clinical skill, 2 and communication skills are used by patients and families as well as certifying and licensing boards as measures of physician competence. 3,4 Observed structured clinical examinations (OSCEs) using standardized patients (SPs) are widely utilized to both teach and assess basic communication skills during medical school. [5][6][7] However, when these students become residents, they are expected to manage clinical situations requiring more advanced communication skills, 1 in which clinicians must navigate emotionally fraught circumstances and in which an intense emotional response from patients or families can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the most important part of the examination is demonstrating the ability to communicate with a patient. A study published in 2014 showed that communication issues were often the top reason for complaints against physicians in North Carolina [12]. Another study showed a modest correlation between Step 2 CS Communication and Interpersonal Skills ratings and the communication skills of interns [13].…”
mentioning
confidence: 99%